Effect of Islamic Entrepreneurship Mind-programming on Entrepreneurial Performance in Jordan - Marwan Alomari, Hadeel; Ibrahim Al-Haddad, Shafig (Jordan Journal of Business Administration, 2024)
The purpose of this study is to explore the Islamic entrepreneurship phenomenon within the Jordanian context by focusing on the individual’s/Muslim mindset and how it affects the success of firms. The paper specifically seeks to examine the effect of Islamic entrepreneurship mind-programming on entrepreneurial performance through entrepreneurial motivation as a mediating variable. This study was conducted in Jordan. The population of the study consists of Muslimpreneurs who met the criteria of being; Muslims and entrepreneurs, working in Jordan and working in a registered company. The study targeted a convenient sample of entrepreneurs (business founders, co-founders, employees, … etc.) in Jordan. A survey questionnaire was adopted for data collection. A sample of 95 respondents was investigated. The SPSS program was used to conduct several methods of analysis, such as simple, multiple and hierarchical regression which aimed to test the study hypotheses. The findings of the study showed that Islamic entrepreneurship mind-programming affects entrepreneurial motivation positively. Entrepreneurial motivation affects entrepreneurial performance positively too. It was also found that entrepreneurial motivation mediates the effect of Islamic entrepreneurship mind-programming on entrepreneurial performance.